Comparative strength of common structural shapes using genetic algorithms - Nadela, Federico Montes
By using Genetic Algorithms, the comparative strength of three (3) common structural shapes (Channel, I-Section and T-Section) under given loading and support conditions were determined. This led to the conclusion that a particular structural shape together with its dimensions will give the optimal solution in beam design in terms of the least cross-sectional area to support the given load, which would then translate to savings in cost and reduction in weight of the structural member. An investigation was also conducted to take into consideration the uncertainties in the dimensions of the structural shapes due to manufacturing limitations and tolerances. This resulted in an assessment of the order of magnitude of this effect on the design variables resulting from minimizing the weighted mean or variance of the fitness function. In solving this optimization problem, a specialized hybrid Genetic Algorithm and Direct Search toolbox within the MATLAB environment was employed.